Hard carbon, preparation method thereof and application of hard carbon in sodium-ion battery
By regulating the parameters of C=O bonds, graphite nitrogen content and ultramicropore tunnel structure in hard carbon, the complex problems of existing carbon material preparation processes are solved, and the hard carbon negative electrode material with high first-efficiency and high-magnification are achieved, which improves the The performance of sodium ion batteries simplifies the preparation process.
Patent Information
- Application Number
- CN202411593479.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing high specific surface area carbon materials have problems such as complex process, cumbersome operation, environmental pollution, high cost and strict equipment requirements during the preparation process, which affects their application in sodium ion batteries.
By regulating the C=O bond content in the oxygen-containing functional groups in hard carbon, the content of graphite nitrogen configuration in nitrogen doping, and the ultramicroporous tunnel structure, hard carbon has high first-week Coulomb efficiency and rate magnification performance. The specific method includes mixing the amine with a halogenated olefin for dehalopolymerization, performing preoxidation and carbonization treatment, and finally obtaining hard carbon by grinding.
It realizes the high first-term efficiency and high-rate performance of hard carbon in sodium ion batteries, improves the energy density and sodium storage performance of sodium ion batteries, and simplifies the preparation process and reduces costs.
Smart Images

Figure CN119481047A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to hard carbon, a preparation method thereof and application in sodium ion batteries, belonging to the technical field of sodium ion batteries, and in particular to a high-initial-efficiency and high-rate hard carbon negative electrode material. Background Art
[0002] The pursuit of a clean, low-carbon, safe, and efficient energy system has significantly driven the development of secondary batteries. As an effective complement to lithium-ion batteries, sodium-ion batteries, with their advantages of readily available raw materials, low cost, low operating potential, wide operating temperature range, and long life, are widely used in large-scale energy storage and low-speed electric vehicles.
[0003] Low-cost, structurally diverse, and environmentally friendly hard carbon is currently the most widely used negative electrode material for sodium batteries. Studies have found that high-specific-surface-area carbon materials combined with rich ultramicroporous channel structures can greatly improve the initial efficiency, capacity, and rate performance of sodium batteries. At the same time, heteroatom doping can also provide additional active sites to further improve the capacity of carbon materials. However, the preparation method of high-specific-surface-area carbon materials usually requires pore-forming activators and templates, and subsequent treatment will use corrosive reagents such as hydrochloric acid and hydrofluoric acid. Therefore, its preparation process has the defects of complex process, cumbersome operation, environmental pollution, high cost, and demanding equipment requirements. Summary of the Invention
[0004] The technical problem solved by the present invention is: to overcome the shortcomings of the existing technology, propose a hard carbon and its preparation method and application in sodium ion batteries, and by regulating the C=O bond content in the oxygen-containing functional groups in the hard carbon, the content of graphitic nitrogen configuration in nitrogen doping and the ultra-microporous tunnel structure, the hard carbon has a higher first-cycle coulombic efficiency and rate performance.
[0005] The technical solution of the present invention is:
[0006] A hard carbon comprising oxygen-containing functional groups, nitrogen elements and a pore structure;
[0007] The oxygen-containing functional group comprises C=O;
[0008] Calculated based on the total mass of the hard carbon being 100%, the mass percentage of oxygen element in the hard carbon is 0.5%-8%;
[0009] Taking the mass of all oxygen elements in hard carbon as 100%, the mass percentage of C=O is 60%-80%; the C=O functional group has reversible adsorption and desorption of sodium ions, which makes the material have a higher reversible sodium storage capacity; by controlling the content of C=O bonds, the sodium ions are reversibly adsorbed and desorbed, and on the basis of ensuring the adsorption and desorption capacity of hard carbon, the high capacity and high initial efficiency of hard carbon are achieved, effectively improving the energy density of sodium ion batteries; oxygen elements can inhibit the transition graphitization of carbon materials and promote the formation of a stable carbon layer structure of hard carbon;
[0010] Calculated based on the total mass of the hard carbon being 100%, the mass percentage of nitrogen in the hard carbon is 0.5%-3%;
[0011] The nitrogen-containing element includes graphitic nitrogen, and the mass percentage of graphitic nitrogen is 85%-95% based on the mass of all nitrogen elements in the hard carbon being 100%. Graphitic nitrogen can make the material have higher conductivity, thereby improving the rate performance of the material. Graphitic nitrogen can take into account both defects and conductivity, thereby ensuring the rate performance of sodium ion batteries. Graphitic nitrogen can effectively improve the conductivity of hard carbon.
[0012] The pore structure is an ultra-microporous tunnel structure with a pore diameter of 0.4nm-0.6nm. This structure enables the hard carbon to have a higher ion diffusion rate and improve the rate performance of the material. In addition, the dense structure of the ultra-microporous tunnel can also effectively improve the compaction density of the hard carbon. The volume of the pore structure is 0.48cm 3 / g-0.93cm 3 / g, which can provide more storage sites for the storage of sodium ions and improve the storage capacity of sodium ions;
[0013] The specific surface area of the hard carbon is 600 m 2 / g-900m 2 / g, which can provide more storage sites for sodium ions, thereby improving the capacity of sodium-ion batteries;
[0014] A method for preparing hard carbon, the method comprising the steps of:
[0015] In the first step, the amine and the halogenated olefin are mixed evenly and subjected to a dehalogenation polymerization reaction to obtain a precursor material;
[0016] In the second step, the precursor material obtained in the first step is subjected to a pre-oxidation treatment;
[0017] The third step is to perform carbonization and grinding to obtain hard carbon.
[0018] In the first step, the amine is at least one of diethylamine, triethylamine, triallylamine, tri-n-butylamine, dibutylamine, triisopropylamine, and triisobutylamine; the halogenated olefin is at least one of hexabromobenzene, hexachlorobenzene, hexachlorobutadiene, and tetrachloroethylene; the molar ratio of the amine to the halogenated olefin is 0.1-8:1; the dehalogenation polymerization reaction temperature is 100-200° C., and the reaction time is 2-6 hours;
[0019] In the second step, the pre-oxidation treatment is carried out in an air atmosphere, at a temperature of 200°C-400°C, at a heating rate of 0.5°C / min-5°C / min, and for a time of 0.5h-2h;
[0020] In the third step, the carbonization treatment temperature is 1000°C-1600°C, the heating rate during the carbonization treatment is 0.5°C / min-5°C / min, and the carbonization treatment time is 1h-3h;
[0021] In the third step, the grinding treatment method is air flow milling, mechanical milling, roller milling or ball milling.
[0022] An application of hard carbon in sodium ion batteries, wherein the obtained hard carbon is coated on a metal substrate such as aluminum foil and dried to obtain an electrode sheet, and the obtained electrode sheet is used as the negative electrode of the sodium ion battery.
[0023] When hard carbon is coated on a metal substrate such as aluminum foil, the hard carbon needs to be made into a coating agent and then coated on the metal substrate such as aluminum foil. The coating agent is a mixture of hard carbon, conductive carbon black (super P) and an aqueous solution of sodium carboxymethyl cellulose (CMC) in a mass ratio of 8:1:1. The concentration of the aqueous solution of sodium carboxymethyl cellulose (CMC) is 1%.
[0024] Beneficial effects
[0025] The present invention provides a high initial efficiency and high rate hard carbon and its application, which relates to the field of battery technology negative electrode. The hard carbon includes oxygen-containing functional groups, nitrogen doping and ultra-microporous tunnel structure. The C=O content accounts for 60%-80% of the total oxygen content, the graphite nitrogen content accounts for 85%-95% of the total content, and the ultra-microporous tunnel structure has a pore volume of 0.48cm 3 / g-0.93cm 3 / g. By regulating the C=O bond, graphitic nitrogen content and pore volume of the ultra-microporous tunnel structure in the hard carbon, the hard carbon has excellent electrochemical properties and is suitable for use as a negative electrode material for high-first-efficiency and high-rate sodium-ion batteries. The hard carbon prepared by the above method includes C=O functional groups, graphitic nitrogen functional groups and ultra-microporous tunnel structures. Therefore, the reversible sodium ion adsorption and desorption ability of the hard carbon and the material conductivity can be improved, and the diffusion of sodium ions can be effectively improved, thereby improving the sodium storage performance of the sodium-ion battery. By controlling the ratio, reaction temperature and reaction time of the dehalogenation polymerization reaction, the dehalogenation polymerization reaction effect can be better, and the controllability during the preparation process is higher, so that hard carbon with high conductivity and sodium ion diffusion rate can be prepared. By carbonizing and grinding the precursor material, the carbonization process can be made more effective to obtain hard carbon. The hard carbon has C=O functional groups, graphitic nitrogen functional groups and ultra-microporous tunnel structures. Thus, the reversible sodium ion adsorption and desorption capacity of hard carbon and the material conductivity can be improved, and the diffusion of sodium ions can be effectively enhanced, thereby improving the sodium storage performance of sodium ion batteries. The electrode material prepared according to the present invention is a hard carbon with C=O functional groups, graphitic nitrogen functional groups and ultra-microporous tunnel structures, which has excellent electrochemical properties and is suitable for application in sodium ion batteries. The electrode sheet made of the hard carbon of the present invention can obtain a sodium ion battery with high first efficiency and good rate performance, and can achieve high specific capacity reversible charge and discharge. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a nitrogen adsorption-desorption curve of the hard carbon Y1 prepared in Example 1;
[0027] Figure 2 Schematic diagram of pore size distribution of hard carbon Y1 prepared in Example 1;
[0028] Figure 3 This is a high-resolution XPS graph of nitrogen element of the hard carbon Y1 prepared in Example 1;
[0029] Figure 4 This is a high-resolution XPS graph of oxygen elements in the hard carbon Y1 prepared in Example 1;
[0030] Figure 5 Schematic diagram of the method of the present invention. DETAILED DESCRIPTION
[0031] The present invention will be described in detail below with reference to the following embodiments, comparative examples and accompanying drawings. It should be understood that these are only for illustration and explanation and are not intended to limit the present invention.
[0032] In the following examples / comparative examples, the charge, discharge and cycle performance tests of the sodium ion battery were performed using a LANDCT2001A tester (Wuhan Landian Electronics Co., Ltd.).
[0033] The present invention describes the structure and composition of hard carbon materials. Figure 1 and Figure 2 Schematic diagram of pore size distribution of nitrogen adsorption-desorption curve of hard carbon Y1 prepared according to Example 1 of the present invention.
[0034] In one embodiment of the present application, the microstructure of the hard carbon may include an ultra-microporous tunnel structure, wherein the pore size of the ultra-microporous tunnel structure in the material is 0.4 nm to 0.6 nm, and the pore volume of the ultra-microporous tunnel is 0.48 cm 3 / g-0.93cm 3 / g. The present application examples do not specifically limit it.
[0035] As an example, the pore volume of the above material is 0.48 cm 3 / g-0.93cm 3 / g. The value of this ratio is typically but not limited to 0.48 cm 3 / g, 0.58cm 3 / g, 0.68cm 3 / g, 0.78cm 3 / g, 0.88cm 3 / g, 0.93cm 3 / g and numbers between any two of the above numbers are all acceptable range values.
[0036] The present invention describes the structure and composition of hard carbon materials. Figure 3 and Figure 4 This is a high-resolution XPS graph of nitrogen and oxygen elements in the hard carbon Y1 prepared according to Example 1 of the present invention.
[0037] In one embodiment of the present application, the microstructure of the hard carbon may include an oxygen-containing functional group structure, and the C=O bond content in the oxygen-containing functional groups in the material is 60%-80%. This embodiment of the present application does not specifically limit this.
[0038] As an example, the C=O bond content of the oxygen-containing functional groups in the above-mentioned material is 60%-80%. Typical but non-limiting values of this ratio include 60%, 65%, 70%, 75%, 80%, and any number between the above two numbers, which are all acceptable ranges.
[0039] In one embodiment of the present application, the microstructure of the hard carbon may include a graphitic nitrogen structure, and the graphitic nitrogen component content in the material accounts for 85%-95% of the total nitrogen content. This embodiment of the present application does not specifically limit this.
[0040] As an example, the graphite nitrogen content in the above material is 85%-95%. Typical but non-limiting values of this ratio can be 85%, 88%, 90%, 92%, 95%, and any number between the above two numbers, all of which are acceptable ranges.
[0041] In some embodiments of the present application, the oxygen content of the hard carbon is 0.5 at % to 8.0 at %, and the nitrogen content of the hard carbon is 0.5 at % to 3.0 at %.
[0042] By maintaining the oxygen and nitrogen contents within the above ranges, the oxygen element can inhibit the transitional graphitization of the carbon material and promote the formation of a stable carbon layer structure in the hard carbon. Graphitic nitrogen can effectively improve the electrical conductivity of the hard carbon.
[0043] As an example, in the embodiments of the present application, the oxygen content of the hard carbon can be measured by X-ray photoelectron spectroscopy to be 0.5 at%-8 at%. Typical, but not limited to, values of this ratio can be 0.5%, 2%, 3.5%, 6%, 8%, and numbers between any two of the above values, all of which are within a desirable range.
[0044] In addition, the nitrogen content of the hard carbon is measured to be 0.5%-3%. The value of this numerical ratio can be typically but not limited to 0.5%, 1%, 1.5%, 2%, 3% and any number between any two of the above values.
[0045] The present invention also provides a method for preparing hard carbon. Figure 5 As shown, the following steps are included:
[0046] S301, uniformly mixing the amine and the halogenated olefin, and performing a dehalogenation polymerization reaction to obtain a precursor material.
[0047] In some embodiments of the present application, a precursor can be prepared first. Specifically, a halogenated olefin is added to a 50 mL reactor, and amines with different substituent groups are added separately. Ultrasonication is performed at room temperature to ensure uniform mixing of the amine and halogenated olefin molecules. The mixed liquid is then subjected to a dehalogenation polymerization reaction, and after cooling to room temperature, a precursor material is obtained. The reaction temperature of the dehalogenation polymerization reaction is 100°C-200°C, and the reaction time is 2h-6h.
[0048] As an example, the reaction temperature of the dehalogenation polymerization reaction is 100° C. to 200° C. Specifically, it can be 100° C., 200° C., or any value between 100° C. and 200° C., such as 110° C., 120° C., 150° C., 180° C., etc., which are not listed here.
[0049] The carbonization treatment time is 2 hours to 6 hours. Specifically, it can be 2 hours, 6 hours, or any value between 2 hours and 6 hours, such as 2.5 hours, 3 hours, 4 hours, 5 hours, etc. These are not listed here.
[0050] In some embodiments of the present application, the amine may include primary, secondary, or tertiary amines, and the amine may have different side chains. Exemplarily, the amine may include at least one of the group consisting of diethylamine, triethylamine, triallylamine, tri-n-butylamine, dibutylamine, triisopropylamine, and triisobutylamine.
[0051] In some embodiments of the present application, the halogenated olefin may be a halogenated reaction monomer having a carbon-carbon double bond. For example, the reaction monomer may include at least one of the group consisting of hexabromobenzene, hexachlorobenzene, hexachlorobutadiene, and tetrachloroethylene.
[0052] It should be noted that the above-mentioned amines and halogenated olefins are merely exemplary, and the embodiments of the present application do not limit the specific implementation methods of the amines and halogenated olefins.
[0053] In some embodiments of the present application, the molar ratio of amine to halogenated olefin is (0.1-8):1.
[0054] As an example, the molar ratio of the amine to the halogenated olefin is (0.1-8):1. This ratio is typical but not limiting, and may be, for example, 0.1:1, 8:1, and any number between any two of the above values, such as 0.5:1, 2:1, 5:1, 7:1, etc. These are not listed here.
[0055] As can be seen from the above, the present invention can adjust the molar ratio between amine and halogenated olefin to achieve a more appropriate content, thereby enabling a sufficient dehalogenation polymerization reaction between the two. Furthermore, a hard carbon anode material having C=O functional groups, graphitic nitrogen functional groups, and an ultra-microporous tunnel structure can be subsequently formed.
[0056] S302. In some embodiments of the present application, the prepared precursor can be pre-oxidized first. Specifically, the precursor material can be pre-oxidized in an air atmosphere, and its temperature can be naturally cooled to room temperature. The pre-oxidation temperature is 200°C-400°C, the pre-oxidation heating rate is 0.5°C / min-5°C / min, and the pre-oxidation time is 0.5h-2h. Then, the precursor material that has been pre-oxidized and cooled to room temperature can be subjected to the next step of heat treatment and then ground to obtain a hard carbon negative electrode material. The precursor material is the oxidation treatment material described above, which will not be repeated here.
[0057] As an example, the pre-oxidation temperature is 200° C. to 400° C. Specifically, it can be 200° C., 400° C., or any value between 200° C. and 400° C., such as 250° C., 280° C., 300° C., 350° C., etc. These are not listed here.
[0058] The above-mentioned pre-oxidation heating rate is 0.5°C / min-5°C / min. Specifically, it can be 0.5°C / min, 5°C / min, or any value between 0.5°C / min and 5°C / min, such as 0.8°C / min, 1.5°C / min, 3.0°C / min, 4.5°C / min, etc. These values are not listed here.
[0059] The pre-oxidation treatment time is 0.5 h to 2 h. Specifically, it can be 0.5 h, 2 h, or any value between 0.5 h and 2 h, such as 0.8 h, 1.2 h, 1.5 h, 1.8 h, etc. These are not listed here.
[0060] S302. In some embodiments of the present application, the prepared precursor can be pre-oxidized first. Specifically, the precursor material can be pre-oxidized in an air atmosphere, and its temperature can be naturally cooled to room temperature. The pre-oxidation temperature is 200°C-400°C, the pre-oxidation heating rate is 0.5°C / min-5°C / min, and the pre-oxidation time is 0.5h-2h. Then, the precursor material that has been pre-oxidized and cooled to room temperature can be subjected to the next step of heat treatment and then ground to obtain a hard carbon negative electrode material. The precursor material is the oxidation treatment material described above, which will not be repeated here.
[0061] As an example, the pre-oxidation temperature is 200° C. to 400° C. Specifically, it can be 200° C., 400° C., or any value between 200° C. and 400° C., such as 250° C., 280° C., 300° C., 350° C., etc. These are not listed here.
[0062] The above-mentioned pre-oxidation heating rate is 0.5°C / min-5°C / min. Specifically, it can be 0.5°C / min, 5°C / min, or any value between 0.5°C / min and 5°C / min, such as 0.8°C / min, 1.5°C / min, 3.0°C / min, 4.5°C / min, etc. These values are not listed here.
[0063] The pre-oxidation treatment time is 0.5 h to 2 h. Specifically, it can be 0.5 h, 2 h, or any value between 0.5 h and 2 h, such as 0.8 h, 1.2 h, 1.5 h, 1.8 h, etc. These are not listed here.
[0064] S303. In some embodiments of the present application, the precursor to be pre-oxidized can be first carbonized at high temperature. Specifically, the precursor material to be pre-oxidized can be carbonized under an inert atmosphere, and its temperature can be naturally cooled to room temperature. The carbonization temperature is 1000°C-1600°C, the pre-oxidation heating rate is 0.5°C / min-5°C / min, and the pre-oxidation time is 1h-3h. Then, the carbon material that has been carbonized and cooled to room temperature can be subjected to the next step of heat treatment and then ground to obtain a hard carbon negative electrode material. The hard carbon negative electrode material is the hard carbon negative electrode material described above, which will not be repeated here.
[0065] As an example, the carbonization treatment temperature is 1000° C. to 1600° C. Specifically, it can be 1000° C., 1600° C., or any value between 1000° C. and 1600° C., such as 1100° C., 1300° C., 1500° C., etc. These are not listed here.
[0066] The above-mentioned pre-oxidation heating rate is 0.5°C / min-5°C / min. Specifically, it can be 0.5°C / min, 5°C / min, or any value between 0.5°C / min and 5°C / min, such as 0.8°C / min, 1.5°C / min, 3.0°C / min, 4.5°C / min, etc. These values are not listed here.
[0067] The pre-oxidation treatment time is 1 hour to 3 hours. Specifically, it can be 1 hour, 3 hours, or any value between 1 hour and 3 hours, such as 1.2 hours, 1.5 hours, 1.8 hours, 2.2 hours, 2.5 hours, 2.8 hours, etc. These are not listed here.
[0068] It can be understood that the calculated values of the above numerical ratios may allow for certain measurement test system errors during actual test operations, and the values within the system error range may be understood as the range defined by the embodiments of the present application.
[0069] In some embodiments of the present application, during the grinding process of the carbonized material, the grinding methods used may include air flow milling, mechanical milling, roller milling, ball milling, etc. The embodiments of the present application do not specifically limit the grinding methods.
[0070] The hard carbon negative electrode material is described below through specific examples.
[0071] Example 1
[0072] S1: triethylamine and hexachlorobutadiene were added to a 50 mL polytetrafluoroethylene reactor, mixed, and ultrasonicated at 25°C for 2 h to form a uniform and stable solution. The reactor was then placed in a stainless steel outer container and reacted at 160°C in a forced air drying oven for 6 h.
[0073] Among them, 24 ml of triethylamine and 4 ml of hexachlorobutadiene (molar ratio 1.25:1);
[0074] S2: After the reaction is completed, the crude product is cooled to room temperature and stored in a vacuum seal;
[0075] S3: The crude product was heat treated in a tube furnace at 300 °C for 1.5 h under air atmosphere;
[0076] S4: The crude product was heated to 1500°C in a vacuum tube furnace under an argon atmosphere at a heating rate of 0.5°C / min for 2 hours to obtain hard carbon Y1 having C=O functional groups, graphitic nitrogen functional groups and ultramicroporous tunnel structure.
[0077] Examples 2-6
[0078] Except that the heat treatment in step S4 was replaced with 1000°C, 1100°C, 1300°C, 1400°C and 1600°C respectively, the rest was the same as Example 1. Examples 2-6 were carried out in sequence; the obtained hard carbons were named Y2, Y3, Y4, Y5 and Y6 respectively.
[0079] Comparative Examples 1-6
[0080] Except that the triethylamine in step S1 was replaced by diethylamine, triallylamine, tri-n-butylamine, dibutylamine, triisopropylamine and triisobutylamine respectively, the rest was the same as Example 1, and Comparative Examples 1-6 were carried out in sequence; the obtained hard carbons were named D1, D2, D3, D4, D5 and D6 respectively.
[0081] Comparative Examples 7-9
[0082] Except that the heating rate in step S4 was replaced by 1°C / min, 3°C / min and 5°C / min respectively, other processes were the same as in Example 1. Comparative Examples 7-9 were carried out in sequence; the obtained hard carbons were named D7, D8 and D9 respectively.
[0083] The hard carbon negative electrode materials prepared in the above Examples 1-6 and Comparative Examples 1-9, as well as the corresponding surface area, pore size distribution, elemental composition characterization, and sodium ion battery performance tests were performed.
[0084] Characterization and test results are shown below:
[0085] Characterization of specific surface area, pore volume, pore size distribution and specific nitrogen / oxygen content of samples Y1-Y6 obtained in Examples 1-6 and samples D1-D9 obtained in Comparative Examples 1-9;
[0086] According to Figure 1Using the same test method, the nitrogen adsorption and desorption curves of Y1-Y6 were obtained. After calculation, it was found that the specific surface area and pore volume of each material were different, as shown in Table 1 below. For the convenience of comparison, the relevant data of Y1 are also listed.
[0087] Table 1: Characterization data of relevant material structure and composition of each sample material
[0088]
[0089]
[0090] In some embodiments of the present application, the technical characteristics of specific surface area, pore volume and pore size distribution are shown in Table 1. It can be seen that the specific surface area of Y1 is as high as 896.4m 2 / g, the material contains a rich ultra-microporous structure, with a pore volume of 0.925cm 3 / g, and the main pore diameters are concentrated around 0.4, 1.5, and 2.5nm. From the data in Table 1, it can be found that comparative examples 1-6 obtain hard carbon by changing the type of amine. It can be found that the surface area and pore volume of the hard carbon prepared by the reaction of primary amines and secondary amines with conjugated halogenated olefins are both smaller. Among the tertiary amines with different branches, triethylamine has the best ultrafine pore size distribution, which can effectively improve the first effect and rate of the material. Comparative examples 7-9 obtain hard carbon by regulating the heating rate and other means. It can be found that the heating rate has a serious effect on the surface area and pore size distribution, the surface area decreases, and the pore size increases. More irreversible adsorption is generated, which reduces the first effect and capacity of the material. In Example 2-6, by regulating the heat treatment temperature, the C=O bond content of oxygen-containing functional groups in the hard carbon, the graphitic nitrogen configuration content during nitrogen doping, and the ultramicroporous tunnel structure were controlled. These parameters were maintained within the desired range for the hard carbon anode material, ensuring higher conductivity, faster sodium ion diffusion, and enhanced sodium ion desolvation. Consequently, the material exhibited higher first-cycle coulombic efficiency and rate capability.
[0091] Electrochemical performance test: In some embodiments of the present application, in order to characterize the effect of the material on improving the electrochemical performance of sodium, the electrode prepared using Y1 was tested for charge and discharge at different current densities in a sodium ion battery. When the discharge current density is 30mA / g, the first efficiency of Y1 can reach 90.9%. The calculated sodium ion battery capacity is 357.2mAh / g, and the battery capacity remains at 108.7mAh / g at a current density of 2A / g. This shows that material Y1 can be charged and discharged at high current density, showing excellent capacity and high-rate charge and discharge performance.
[0092] It can be seen from this that the hard carbon negative electrode obtained according to the present invention having C=O functional groups, graphitic nitrogen functional groups and ultra-microporous tunnel structure has excellent electrochemical properties, and can be used as a battery negative electrode material, especially an electrode material for sodium ion batteries, and has good application prospects and industrial production potential in the field of electrochemical energy storage.
[0093] Electrochemical Performance Characterization of Samples Y1-Y6 from Examples 1-6 and Samples D1-D9 from Comparative Examples 1-9: Battery electrodes obtained from Y1-Y6 and D1-D9 were tested, and calculations revealed that the initial efficiency, reversible capacity, and rate performance of each material in a sodium-ion battery at current densities of 30 mA / g and 2 A / g, respectively, are shown in Table 2 below. For ease of comparison, the performance of Y1 in a sodium-ion battery is also listed.
[0094] Table 2: Capacity and initial efficiency of each sample material at different current densities in sodium ion batteries
[0095] sample First effect (%) Reversible capacity (mAh / g) Rate performance (mAh / g@2A / g) Y1 90.9 357.2 108.7 Y2 80.1 314.9 101.8 Y3 87.1 321.1 94.3 Y4 87.9 312.8 101.2 Y5 85.8 324.4 95.3 D1 79.0 286.1 29.4 D2 76.3 298.4 45.7 D3 73.2 302.3 47.2 D4 71.9 301.6 46.4 D5 76.6 283.7 38.7 D6 67.8 189.3 54.2 D7 88.7 203.6 74.4 D8 47.2 291.7 64.7 D9 78.9 223.1 58.4
[0096] This application provides a method for preparing hard carbon anode materials using amines and halogenated olefins as starting materials and regulating the polymer structure through dehalogenation polymerization. By exploring the structure-activity relationship between the proportions of C=O bonds and graphitic nitrogen configurations in oxygen and nitrogen elements, respectively, and the specific surface area and pore volume, and sodium storage performance in the hard carbon, the optimal parameter range for excellent sodium storage performance was determined, ensuring high electron transport properties and fast ion diffusion rate in the hard carbon, thereby improving the overall sodium storage performance of the hard carbon.
[0097] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A hard carbon, characterized in that: The hard carbon includes oxygen-containing functional groups, nitrogen elements and pore structures; The oxygen-containing functional group comprises C=O; Calculated based on the total mass of the hard carbon being 100%, the mass percentage of oxygen element in the hard carbon is 0.5%-8%; Taking the mass of all oxygen elements in hard carbon as 100%, the mass percentage of C=O is 60%-80%; Taking the total mass of the hard carbon as 100%, the mass percentage of the nitrogen element in the hard carbon is 0.5%-3%; The nitrogen element comprises graphitic nitrogen, and the mass percentage of graphitic nitrogen is 85%-95% when the mass of all nitrogen elements in the hard carbon is 100%; The pore structure is an ultra-microporous tunnel structure with a pore diameter of 0.4nm-0.6nm and a volume of 0.48cm 3 / g-0.93cm 3 / g.
2. A hard carbon according to claim 1, characterized in that: The specific surface area of the hard carbon is 600 m 2 / g-900m 2 / g.
3. A method for preparing hard carbon, characterized in that The steps of the method include: In the first step, amine and halogenated olefin are mixed to undergo dehalogenation polymerization to obtain a precursor material; In the second step, the precursor material obtained in the first step is subjected to a pre-oxidation treatment; In the third step, the product after the pre-oxidation treatment in the second step is first carbonized and then ground to obtain hard carbon.
4. The method for preparing hard carbon according to claim 3, characterized in that: In the first step, the amine is at least one of diethylamine, triethylamine, triallylamine, tri-n-butylamine, dibutylamine, triisopropylamine, and triisobutylamine; the halogenated olefin is at least one of hexabromobenzene, hexachlorobenzene, hexachlorobutadiene, and tetrachloroethylene; the molar ratio of the amine to the halogenated olefin is 0.1-8:1; the dehalogenation polymerization reaction temperature is 100-200°C, and the time is 2-6h.
5. A method for preparing hard carbon according to claim 3 or 4, characterized in that: In the second step, the pre-oxidation treatment is carried out in an air atmosphere, at a temperature of 200°C-400°C, at a heating rate of 0.5°C / min-5°C / min, and for a time of 0.5h-2h.
6. The method for preparing hard carbon according to claim 5, characterized in that: In the third step, the carbonization treatment temperature is 1000° C.-1600° C., the heating rate during the carbonization treatment is 0.5° C. / min-5° C. / min, and the carbonization treatment time is 1 h-3 h.
7. The method for preparing hard carbon according to claim 3, characterized in that: In the third step, the grinding treatment method is air flow milling, mechanical milling, roller milling or ball milling.
8. Application of hard carbon in sodium ion battery, characterized in that: The obtained hard carbon is made into a coating agent, which is coated on a metal substrate and dried to obtain an electrode sheet, and the obtained electrode sheet is used as a negative electrode of a sodium ion battery.
9. The use of hard carbon in sodium ion batteries according to claim 8, characterized in that: The coating agent is prepared by mixing hard carbon, conductive carbon black (super P) and an aqueous solution of sodium carboxymethyl cellulose (CMC) in a mass ratio of 8:1:1, and the concentration of the aqueous solution of sodium carboxymethyl cellulose (CMC) is 1%.
10. The use of hard carbon in sodium ion batteries according to claim 8 or 9, characterized in that: The metal substrate is aluminum foil.
Citation Information
Patent Citations
High-capacity sodium ion battery hard carbon negative electrode material and preparation method thereof
CN116207260A
Hard carbon material and preparation method and application thereof
CN116947009A
High-carbon-yield nitrogen-doped sodium ion battery hard carbon negative electrode material and preparation method thereof
CN118026145A
Automatic electric pressure cooker
KR1020240030118A
Cited By
Battery and electric device
WO2026194469A1